Ranibizumab versus bevacizumab to treat neovascular age-related macular degeneration: one-year findings from the IVAN randomized trial. - Chakravarthy, U; Harding, S; Rogers, C; Downes, S; Lotery, A; Wordsworth, S; Reeves, B (2012)
PURPOSE: To compare the efficacy and safety of ranibizumab and bevacizumab intravitreal injections to treat neovascular age-related macular degeneration (nAMD). DESIGN: Multicenter, noninferiority factorial trial with equal allocation to groups. The noninferiority limit was 3.5 letters. This trial is registered (ISRCTN92166560). PARTICIPANTS: People >50 years of age with untreated nAMD in the study eye who read ≥ 25 letters on the Early Treatment Diabetic Retinopathy Study chart. METHODS: We randomized participants to 4 groups: ranibizumab or bevacizumab, given either every month (continuous) or as needed (discontinuous), with monthly review. MAIN OUTCOME MEASURES: The primary outcome is at 2 years; this paper reports a prespecified interim analysis at 1 year. The primary efficacy and safety outcome measures are distance visual acuity and arteriothrombotic events or heart failure. Other outcome measures are health-related quality of life, contrast sensitivity, near visual acuity, reading index, lesion morphology, serum vascular endothelial growth factor (VEGF) levels, and costs. RESULTS: Between March 27, 2008 and October 15, 2010, we randomized and treated 610 participants. One year after randomization, the comparison between bevacizumab and ranibizumab was inconclusive (bevacizumab minus ranibizumab -1.99 letters, 95% confidence interval [CI], -4.04 to 0.06). Discontinuous treatment was equivalent to continuous treatment (discontinuous minus continuous -0.35 letters; 95% CI, -2.40 to 1.70). Foveal total thickness did not differ by drug, but was 9% less with continuous treatment (geometric mean ratio [GMR], 0.91; 95% CI, 0.86 to 0.97; P = 0.005). Fewer participants receiving bevacizumab had an arteriothrombotic event or heart failure (odds ratio [OR], 0.23; 95% CI, 0.05 to 1.07; P = 0.03). There was no difference between drugs in the proportion experiencing a serious systemic adverse event (OR, 1.35; 95% CI, 0.80 to 2.27; P = 0.25). Serum VEGF was lower with bevacizumab (GMR, 0.47; 95% CI, 0.41 to 0.54; P<0.0001) and higher with discontinuous treatment (GMR, 1.23; 95% CI, 1.07 to 1.42; P = 0.004). Continuous and discontinuous treatment costs were £9656 and £6398 per patient per year for ranibizumab and £1654 and £1509 for bevacizumab; bevacizumab was less costly for both treatment regimens (P<0.0001). CONCLUSIONS: The comparison of visual acuity at 1 year between bevacizumab and ranibizumab was inconclusive. Visual acuities with continuous and discontinuous treatment were equivalent. Other outcomes are consistent with the drugs and treatment regimens having similar efficacy and safety. FINANCIAL DISCLOSURE(S): Proprietary or commercial disclosures may be found after the references.